The Role Of Work Productıvıty Medıatıon Between Work From Home And Workload On Employee Performance CV. NEO - Robby Sandhi Dessyarti; Erna Diyah Aria Santi (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to empirically prove the mediating role of work productivity between work from home and workload on the performance of CV NEO employees uses the saturated sampling method, where the number of employees is 69 people. This research method uses a quantitative approach using the Smart PLS version 3 software. The results show that work from home has an effect on work productivity, work from home has an effect on employee performance, the workload does not have a significant effect on work productivity, the workload has a significant effect on employee performance, work productivity can mediate the relationship between work from home and employee performance, work productivity cannot mediate the relationship between workload and employee performance